2021
DOI: 10.1146/annurev-publhealth-100119-113802
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality in Africa: Public Health Implications

Abstract: This review highlights the importance of air quality in the African urban development process. We address connections between air pollution and ( a) rapid urbanization, ( b) social problems, ( c) health impacts, ( d) climate change, ( e) policies, and (  f ) new innovations. We acknowledge that air pollution levels in Africa can be extremely high and a serious health threat. The toxic content of the pollution could relate to region-specific sources such as low standards for vehicles and fuels, cooking with sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 117 publications
(136 reference statements)
0
61
0
Order By: Relevance
“…These pollutants are generated from natural events, such as fires, storms, volcanic eruptions, and the release of pollen. Furthermore, a major source of air pollutants is human activity, such as fossil fuel combustion, agricultural activity, manufacturing (particularly in the form of factory exhausts), and mining [1][2][3]. Exposure to air pollutants is associated with many diseases, including cardiovascular diseases, neurodegenerative diseases, diabetes, and glaucoma [1,2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These pollutants are generated from natural events, such as fires, storms, volcanic eruptions, and the release of pollen. Furthermore, a major source of air pollutants is human activity, such as fossil fuel combustion, agricultural activity, manufacturing (particularly in the form of factory exhausts), and mining [1][2][3]. Exposure to air pollutants is associated with many diseases, including cardiovascular diseases, neurodegenerative diseases, diabetes, and glaucoma [1,2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, greater availability of air pollution statistics can contribute to enhancing public concern, which would in turn lead to primary demand for and the development of clean air strategies [ 19 ]. Other benefits of managing air pollution also include the drive for other positive changes, such as in health, well-being, and climate [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Burden of disease (BoD) estimations by AirQ+ as total mortality number of attributable cases and mortality number of attributable cases per 100,000 population at risk, using age-standardized and crude mortality rates per 100,000 women in Ethiopia, Africa.Disease burden DALYs estimations of attributable cases for the study representative population using DALYs per 100,000 women of all ages in Ethiopia are20,566 (95% CI: 15,632-23,922) for ALRI, 15,541 (95% CI: 10,846-19,243) for COPD, (95% CI: 25,316-51,897) for IHD, 13,923 (95% CI: 7701-16,195) for lung cancer and (95% CI: 23,308-51,656) for stroke. These estimated attributable cases are lower if only women aged 49 and under are considered (…”
mentioning
confidence: 99%
“…Sub-Saharan Africa is urbanising at an unprecedented rate and is projected to pass the 50% urban tipping point by 2035 [ 38 ]. This rapid urbanisation, together with inadequate capacities in policy regulations and supporting infrastructure, are expected to bring unfavourable changes in urban environment, including the air quality [ 39 ]. Some African cities already reported that concentrations of air pollutants were higher in urban business and high-density residential areas, where traffic and biomass use are the dominant sources, than in peri-urban or rural areas where traffic is considerably less [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%